Expression of Novel L-Leucine Dehydrogenase and High-Level Production of L-Tert-Leucine Catalyzed by Engineered Escherichia coli - Jia, Yuan-Yuan; Xie, Yu-Li; Yang, Lu-Lu; Shi, Hong-Ling; Lu, Yun-Feng; Zhang, Si-Pu; Tang, Cun-Duo; Yao, Lun-Guang; Kan, Yun-Chao (Frontiers in Bioengineering and Biotechnology, 2021)
Leucine dehydrogenase (LDH) is a NAD+-dependent oxidoreductase, which can selectively catalyze α-keto acids to obtain α-amino acids and their derivatives. It plays a key role in the biosynthesis of L-tert-leucine (L-Tle). As a non-naturally chiral amino acid, L-Tle can be used as an animal feed additive, nutrition fortifier, which is a perspective and important building block in the pharmaceutical, cosmetic and food additive industry. In this study, four hypothetical leucine dehydrogenases were discovered by using genome mining technology, using the highly active leucine dehydrogenase LsLeuDH as a probe. These four leucine dehydrogenases were expressed in Escherichia coli BL21 respectively, and purified to homogeneity and characterized. Compared with the other enzymes, the specific activity and Kcat/Km value of PfLeuDH are also shows stronger advantage. In addition, the highly selective biosynthesis of L-Tle from trimethylpyruvic acid (TMP) was successfully carried out by whole-cell catalysis using engineered E. coli cells as biocatalyst, which can efficiently co-express leucine dehydrogenase and formate dehydrogenase. 100 mM TMP was catalyzed for 24 hours, the yield and space-time yield of L-Tle reached 87.38% (e.e.>99.99%) and 10.90 g·L-1·d-1. In short, this research has initially achieved the biosynthesis of L-Tle, laying a solid foundation for the realization of low-cost and large-scale biosynthesis of L-Tle.